Effect of Compesation on Employee Performance - Jaenudin Akhmad; Ria Estiana; Muhamad Rusdiana (Best Journal of Administration and Management, 2023)
In a company, employee performance is very influential on company development and one of the factors that affect performance is compensation with various indicators. The formulation of the problems in this study are (1) How is the application of compensation to company?, (2) What factors affect employee performance at company? , (3) How does compensation affect employee performance at company? This study aims to determine how much influence there is on compensation on employee performance at company. The data used is through a questionnaire by taking 30 employees as a sample and measured using a Likert scale. Answers from strongly disagree to strongly agree. The data were processed using SPSS and the data used were quantitative analysis and were processed using quantitative methods of analysis and simple linear regression analysis. Form of Compensation at company does not only cover the matter of wages / salaries but the provision of facilities and allowances provided by the company to have an effect on the performance of every employee at company.